Scythian Art in Gandhara: A Case Study of the so-called Gold Girdle from Pattan (Kohistan) - Hameed, Muhammad (Ancient Pakistan, 2021)
Among innumerable finds and antiquities discovered from Gandhara, the gold girdle from Pattan, Kohistan is exceptional and incomparable. It is not only valuable in term of metal but also equally significant for the sophisticated iconography, never witnessed in Gandhara before. The profusely decorated and carved gold girdle, under discussion, is the perfect example of the animal style, usually associated with Scythians. The main focus on the present paper is to make comprehensive examination of the animal iconography by making comparative analysis with the archaeological evidences from Eurasian Steppes. In the end some aspects related to study of the gold girdle, its proposed function, dating and impact on Gandharan artistic traditions will also be discussed.